2023
DOI: 10.1111/jir.13042
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient status in children and adolescents with Down syndrome: systematic review and meta‐analysis

Abstract: Background Down syndrome (DS) is the most common genetic disorder. To date, the scientific literature regarding micronutrient status in children and adolescents with DS has not been systematically reviewed. Therefore, our aim was to provide a systematic review and meta-analysis on this topic. Methods We identified all relevant case-control studies published by 1 January 2022, by searching the PubMed and Scopus databases for original English-language articles analysing the micronutrient status of individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is involved in the maintenance and development of both innate and adaptive immune systems ( 11 ), and its deficiency results in an altered host defense, increased risk of inflammation and even death. In subjects with DS a decreased concentration of this element in serum, plasma and whole blood is reported ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is involved in the maintenance and development of both innate and adaptive immune systems ( 11 ), and its deficiency results in an altered host defense, increased risk of inflammation and even death. In subjects with DS a decreased concentration of this element in serum, plasma and whole blood is reported ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to meta-analysis by Barišić and Saghazadeh, zinc concentration was significantly lower in serum, plasma and whole blood of children and adolescents with trisomy 21 compared to control group ( 12 , 13 ) instead copper (Cu) and zinc levels were higher in trisomic red blood cells ( 12 ). This meta-analysis showed that females and males with trisomy 21 do not differ in Zinc levels and evidence was not conclusive with regards to the effect of age on zinc levels ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation